RIG-I agonist SLR10 promotes macrophage M1 polarization during influenza virus infection - Wu, Wenxin; Zhang, Wei; Alexandar, Jeremy S.; Booth, J. Leland; Miller, Craig A.; Xu, Chao; Metcalf, Jordan P. (Frontiers in Immunology, 2023)
RATIONALE: A family of short synthetic, triphosphorylated stem-loop RNAs (SLRs) have been designed to activate the Retinoic-acid-inducible gene I (RIG-I) pathway and induce a potent interferon (IFN) response, which may have therapeutic potential. We investigated immune response modulation by SLR10. We addressed whether RIG-I pathway activation with SLR10 leads to protection of nonsmoking (NS) and cigarette smoke (CS)-exposed mice after influenza A virus (IAV) infection. METHODS: Mice were given 25 µg of SLR10 1 day before IAV infection. We compared the mortality and host immune responses of NS and CS-exposed mice following challenge with IAV. RESULTS: SLR10 significantly reduced weight loss and improved survival in both NS and CS-exposed mice during IAV infection. SLR10 administration repaired the impaired proinflammatory response in CS-exposed mice without causing more lung injury in NS mice as assessed by physiologic measurements. Although histopathologic scoring of the cardinal features of IAV infection revealed that SLR10 appeared to result in higher overall pathological scores than untreated groups in both NS and CS mice, this change was not enough to increase lung injury evaluated by lung-to-body weight ratio. Both qRT-PCR on lung tissues and multiplex immunoassay on bronchoalveolar lavage fluids (BALFs) showed that most IFNs and proinflammatory cytokines were expressed at lower levels in SLR10-treated NS mice than control-treaded NS mice at day 5 post infection (p.i.). Remarkably, proinflammatory cytokines IL-6, IL-12 and GM-CSF were increased in CS-exposed mice by SLR10 at day 5 p.i. Significantly, SLR10 elevated the ratio of the two chemokines (CXCL9: CCL17) in BALFs, suggesting macrophages were polarized to classically activated (M1) status. In vitro testing also found that SLR10 not only stimulated human alveolar macrophage polarization to an M1 phenotype, but also reversed cigarette smoke extract (CSE)-induced M2 to M1 polarization. CONCLUSIONS: Our results demonstrate that SLR10 administration in mice is protective for both NS and CS-exposed IAV-infected mice. Mechanistically, SLR10 treatment promoted M1 macrophage polarization in the lung during influenza infection. The protective effects by SLR10 may be a promising intervention for therapy for infections with viruses, particularly those with CS-enhanced susceptibility to adverse outcomes.